Prevalence and association of non-alcoholic fatty liver disease and insulin resistance among non-diabetic obese, overweight, and metabolically obese normal-weight adult patients attending at a tertiary care hospital in Eastern India - Samik Pramanik; Jimmy Barua; Lokanathan V; Sharmistha Roy (Asian Journal of Medical Sciences, 2025)
Background: Worldwide, the incidence of obesity, overweight, and metabolic syndrome is dramatically increasing. Non-alcoholic fatty liver disease (NAFLD) is associated with both obesity/overweight and metabolic syndrome. Aims and Objectives: The aim of this study is to assess non-invasively the prevalence and association of NAFLD and insulin resistance among non-diabetic obese, overweight, and metabolically obese normal-weight (MONW) adults. Materials and Methods: This single-center cross-sectional study included 137 subjects aged more than 18 years, out of which 50 were obese, 22 were overweight, and 31 MONW. All subjects underwent detailed history, complete physical examination, laboratory test, and grading of hepatic fat by ultrasonography. Results: The mean age (mean± standard deviation) of the patients was 36.91±11.01 years with a range of 18–67 years. 53 (38.7%) and 84 (61.3%) of the patients were male and female, respectively. Out of the 137 patients, 73 (53.3%) of patients had NAFLD. The prevalence of NAFLD was significantly higher in the obese group (56.2%) as compared to others (Z=5.56; P<0.0001). The prevalence of NAFLD among overweight, MONW, and normal body mass index (BMI) were 17.8%, 19.2%, and 6.8%, respectively. The proportion of Grade-1 and Grade-2 NAFLD was significantly higher than that of Grade-3 (Z=4.16; P<0.0001). There was a significant association between BMI, insulin resistance measured by homeostasis model assessment-estimated insulin resistance (HOMA-IR), and grade of fatty liver of the patients (P<0.0001). Conclusion: NAFLD is more prevalent in obese than other groups. The grade of fatty liver has a significant association with HOMA-IR and BMI.